ANALISIS SWOT PADA UMKM B’STEAK GRILL UNTUK MENINGKATKAN STRATEGI PENJUALAN - Anna Wijayanti; Tyna Yunita; Muhamad Elzan Musyafa; Nurul Cahyani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
In Indonesia, the development of the culinary business is progressing quite rapidly even though the economic situation in Indonesia is currently experiencing quite difficult times. Along with the increase in businesses in the culinary field, it causes competition between entrepreneurs engaged in the same field. SWOT is a tool that can be used to determine the strengths and weaknesses of a company, especially in the field of marketing. This research was conducted in the Marakash Square area, Kec. Babylon, Kab. North Bekasi at B'Steak Grill. By utilizing promotions through social media such as Instagram, Facecook and Whatsapp. By establishing this business in Marakash Square because the location is very strategic and is visited by many local people.